Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/pmic.201900042
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Cancer Metabolomics

Abstract: Challenges in metabolomics for a given spectrum of disease are more or less comparable, ranging from the accurate measurement of metabolite abundance, compound annotation, identification of unknown constituents, and interpretation of untargeted and analysis of high throughput targeted metabolomics data leading to the identification of biomarkers. However, metabolomics approaches in cancer studies specifically suffer from several additional challenges and require robust ways to sample the cells and tissues in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 127 publications
(112 reference statements)
0
56
0
Order By: Relevance
“…The process of LM of CRC is extremely complex, involving many tumor-related molecules, which are induced and regulated by their respective specific signaling pathways. With the continuous progress of all kinds of research techniques in recent years, a growing body of evidence has shown that tumor development and metastasis are related to the cancer genome (16), transcriptome (17), epigenetics (18), proteome (19), metabolome (20), and tumor microenvironment (21) interaction cross-regulation of a dynamic complex process.…”
Section: Discussionmentioning
confidence: 99%
“…The process of LM of CRC is extremely complex, involving many tumor-related molecules, which are induced and regulated by their respective specific signaling pathways. With the continuous progress of all kinds of research techniques in recent years, a growing body of evidence has shown that tumor development and metastasis are related to the cancer genome (16), transcriptome (17), epigenetics (18), proteome (19), metabolome (20), and tumor microenvironment (21) interaction cross-regulation of a dynamic complex process.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that 10 metabolites were different between early-stage PDAC and IPMN, and that PCA could be a useful tool for early diagnosis of PDAC. Challenges in metabonomics include compound annotation, identification of unknown constituents, accurate measurement of metabolite abundance, and analysis of high-throughput metabonomics data [55] . Additionally, metabonomics in cancer research specifically requires robust ways to collect samples in order to precisely and effectively profile the heterogeneous tumor environment [55] .…”
Section: Metabonomicsmentioning
confidence: 99%
“…Challenges in metabonomics include compound annotation, identification of unknown constituents, accurate measurement of metabolite abundance, and analysis of high-throughput metabonomics data [55] . Additionally, metabonomics in cancer research specifically requires robust ways to collect samples in order to precisely and effectively profile the heterogeneous tumor environment [55] . Overall, metabonomics allows researchers to identify novel biomarkers that were not previously known to be involved in PDAC carcinogenesis and development.…”
Section: Metabonomicsmentioning
confidence: 99%
“…Advanced technologies, including metabolomics (8) and metabolic flux analysis (9), are key to decode the heterogeneous metabolic preferences and dependencies of tumors in vivo, but they can only be performed in a very limited number of patients given the high costs of the equipment and the level of specialization of personnel involved in this type of analysis. Moreover, these techniques do not enable to study intra-tumor metabolic heterogeneity as they assess levels of metabolites in whole tumor lysates or track the incorporation of a labeled substrate into downstream metabolites.…”
Section: Introductionmentioning
confidence: 99%